Nutritional, Bioactive, and Flavor Components of Giant Stropharia (Stropharia rugoso-annulata): A Review - Lei Huang; Chunmei He; Can Si; Hongyu Shi; Jun Duan (Journal of Fungi, 2023)
Giant Stropharia (S. rugoso-annulata) is an edible mushroom recommended for consumption by the Food and Agriculture Organization of the United Nations. It possesses significant culinary and medicinal functionalities. The characteristics of this mushroom include high protein content, abundant bioactive compounds, delicious and sweet taste, and pleasant aroma. In recent years, the S. rugoso-annulata industry has seen strong growth, especially in China. This article presents the first comprehensive and systematic review of the nutritional, bioactive, and flavor components of S. rugoso-annulata, as well as their influencing factors. This article provides scientific evidence for the production of high-quality S. rugoso-annulata mushrooms, the extraction of bioactive components, post-harvest storage, and culinary processing, aiming to promote the consumption of S. rugoso-annulata and the health of consumers.